Ekofeminisme: Suatu Tawaran Solusi Mengatasi Krisis Moral - hasim, sarifa suhra (PSW, 2012)
Abstract: This paper examines about ekofeminism that is a solution overcome moral crisis. The offered issues are what is the background of the emergence ekofeminism theory and how can it be used as a solution to overcome ekofeminism moral crisis.This is due to the assumption and the reality that modern human civilization both men and woman are seen to dominate , dominate, exploit. Atahe destruction of nature, pollution, rape of nature, crime, degradation of social solidarity, is a small example of that happening lately. On the basis of moral breakdown, the feminists who are increasingly aware that modern civilization has been so out of balance, too heavy on the quality of the masculine and less on quality of feminism such as love, concern, care and maintenance.Ekofeminism want respect for nature and respect for the institusion of family so that children are maintained and educated well in order to be a well character generation and care so as to create a balnce between feminime and masculine qualities in society.